Application of the Graphic Organizer Method in Improving Students' Reading Comprehension of Narrative Text - Rizqi Abdul Majid; Riyadi, Arie Rahkmat; Kurniawan, Haviz (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research addresses the issue of students struggling with reading and comprehending narrative texts. Its objective is to enhance the reading comprehension of 5th-grade elementary school students by employing the graphic organizer method. This method emphasizes the creation of concept maps or charts to aid in understanding the narrative texts. The research follows a classroom action research approach, consisting of two cycles with one meeting each. Each cycle involves lesson planning, implementation, and assessment using teaching modules. The findings reveal that in the first cycle, out of 20 students evaluated, 10 achieved scores above the passing grade, while 10 scored below it. Consequently, a second cycle of learning was conducted. In the second cycle, out of 28 students, 23 obtained scores above the passing grade, with 5 scoring below it. Thus, 82% of the students attained scores above the passing grade. These results highlight the effectiveness of the graphic organizer method in improving the reading comprehension of narrative texts among 5th-grade elementary school students.